Recommendations and Guidelines for the Use of Simulation to Address Structural Racism and Implicit Bias. Issue 4 (August 2021) - Vora, Samreen; Dahlen, Brittany; Adler, Mark; Kessler, David O.; Jones, V. Faye; Kimble, Shelita; Calhoun, Aaron
Abstract : Summary Statement: Simulation-based education is a particularly germane strategy for addressing the difficult topic of racism and implicit bias due to its immersive nature and the paradigm of structured debriefing. Researchers have proposed actionable frameworks for implicit bias education, particularly outlining the need to shift from recognition to transformation, with the goal of changing discriminatory behaviors and policies. As simulation educators tasked with training health care professionals, we have an opportunity to meet this need for transformation. Simulation can shift behaviors, but missteps in design and implementation when used to address implicit bias can also lead to negative outcomes. The focus of this article is to provide recommendations to consider when designing simulation-based education to specifically address racism and implicit bias. Abstract : Supplemental digital content is available in the text.